Postoperative assessment and management of complications - HSTN (Carrollton : HSTN, 2000)
This video shows how to perform a postoperative assessment using the Airway, Breathing, and Circulation (ABC's) technique. It demonstrates both the primary survey (used to admit and assess a postoperative patient) and the more detailed secondary survey, which gathers in-depth pulmonary, circulatory, and neurological assessment information. It discusses common postoperative pulmonary and circulatory complications and describes signs that indicate a complication may become an emergency
Keywords: Postoperative Care -- nursing; Postoperative Complications -- nursing; Nursing Assessment -- methods; Catheterization, Peripheral -- nursing